The Implementation of ‘Market Day' Activities to Improve Children Entrepreneurship at Telkom Preschool Ternate - Samad, Farida; Wondal, Rosita; Mahmud, Nurhamsa; Haryati, Haryati; Purba, Natalina (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aims to describe the implementation of 'market day' activities to improve children entrepreneurship learning at Telkom Preschool Ternate. The research method used is descriptive qualitative. The subjects of this research were students and teachers of group B Telkom Preschool in academic year 2019/2020. Data collection used direct observation, in-depth interviews and documentary methods. The data were analyzed qualitatively with such stages of reduction, presentation of data, verification and conclusion. The result showed that the implementation of the 'market day' or school market activities in Telkom preschool Ternate has integrated with entrepreneurial values based on Telkom preschool curriculum. The students were able to get direct experience about entrepreneurship value. All students in A1, A2, A3, B1, B2, B3 groups felt enthusiastic and motivated when buying and selling activities. The learning activities from the beginning to the end were done in accordance with the principles of learning for early childhood and directed towards the achievement of learning objectives. Thus, it will improve children's cognitive abilities and entrepreneurial skills from an early age.